2013
DOI: 10.1167/iovs.13-12296
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anti-Inflammatory Effects in Rabbit Eye Model Using Biodegradable Poly Beta-Amino Ester Nanoparticles of Triamcinolone Acetonide

Abstract: It can be concluded that polymeric nanoparticles of triamcinolone acetonide will provide as good an anti-inflammatory effect as the subconjunctival injection method and are better compared with other drug delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Interestingly, the number of immuno-positive nuclei in the peripheral cornea of the group treated with the TA-loaded PEG2- b -PLA1 micelles suspended in chitosan hydrogel (group IV) was very scarce ( Figure 5(D) ). These results are in agreement with previous reports which showed that mucoadhesive nanoparticles of TA had better anti-inflammatory effect in the rabbit eyes compared with the drug suspension (Sabzevari et al., 2013a ). The enhanced anti-inflammatory efficacy of TA micelles suspended in chitosan hydrogel compared to all other formulations could be attributed to several factors.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Interestingly, the number of immuno-positive nuclei in the peripheral cornea of the group treated with the TA-loaded PEG2- b -PLA1 micelles suspended in chitosan hydrogel (group IV) was very scarce ( Figure 5(D) ). These results are in agreement with previous reports which showed that mucoadhesive nanoparticles of TA had better anti-inflammatory effect in the rabbit eyes compared with the drug suspension (Sabzevari et al., 2013a ). The enhanced anti-inflammatory efficacy of TA micelles suspended in chitosan hydrogel compared to all other formulations could be attributed to several factors.…”
Section: Resultssupporting
confidence: 94%
“…The drug loading capacity observed in this study is higher than that observed for other drugs encapsulated into polymeric micelles, which typically falls in the range of 5–10% w/w (Kim et al., 2010 ; Shen et al., 2017 ). Other polymeric nanoparticle formulations, such as those of poly( D,L -lactide-co-glycolide) (PLGA) and poly β-amino ester showed low TA loading capacity in the range of ∼1–5% (Sabzevari et al., 2013a , b ). High drug loading capacity observed in this study is advantageous since it limits the needed amounts of carrier polymers, which in turn limits the unnecessary burden of degrading, metabolizing and excreting the polymers from the body (Shen et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TA inhibits the expression of intraocular neovascularization and inflammation 18 , 19 . The evaluation of TA injection on PGE2, HIF-1α, and VEGF concentrations in the aqueous and vitreous humor showed that the concentration of HIF-1α in the aqueous humor decreased at 12 h after TA injection.…”
Section: Discussionmentioning
confidence: 99%
“…Topically administered dorzolamide hydrochloride and timolol maleate have been shown to significantly reduce IOP in rabbits more and with a longer sustained effect when loaded in hyaluronic acid-modified chitosan nanoparticles compared to a marketed free drug formulation (Table 2) [33]. Polymeric nanoparticles loaded with various corticosteroids and administered through multiple routes including intravenous, topical, and subconjunctival, have been demonstrated to effectively reduce inflammation in animal models of uveitis [34][35][36]. When administered intravenously, nanoparticles formed from a co-polymer of poly(lactic acid) (PLA) and PEG, loaded with betamethasone phosphate, could effective distribute to the eyes of rats with experimental autoimmune uveoretinitis and reduce inflammatory symptoms for up to 14 d (Table 2) [34].…”
Section: Clinical Applicationsmentioning
confidence: 99%